Modifikasi Sistem Counter Length Tread Pada Mesin Building PT ASD - Surhayati; Susilo Wardoyo, Adik; Samudra Hidayah, Ihsan; Zacky, Muhammad Farid (Jurnal Instrumentasi dan Teknologi Informasi (JITI), 2025)
The positioning system for the photocell on the PT ASD tire building machine's tread counter length is still manually operated and relies on the operator's intuition. The operator needs several attempts to adjust the photocell's position to produce tread cuts that meet specifications. These repeated trials result in an average of about 75% NG (Not Good or failed) tread from the total number of trials conducted in one tread length adjustment process. In this paper, the author modifies the tread counter length system to change the manual system into an automatic one that can accurately determine the photocell position to achieve the desired tread cut length. The control system created consists of a PLC as the main controller, an encoder as the position reader, and an inverter and electric motor as the photocell movers. Based on testing results after the modification, a photocell positioning accuracy of 99.5% was achieved, and the occurrence of NG tread during adjustment decreased by 60.72%.